2017
DOI: 10.1080/16184742.2017.1314530
|View full text |Cite
|
Sign up to set email alerts
|

Marketing outsourcing in the English Premier League: the rights holder/agency interface

Abstract: Research question: While marketing outsourcing may offer a clear means for revenue generation and cost efficiency, there is a need to go beyond the outsourcing decision itself to address 'how' outsourcing can be managed successfully. Differing to existing studies, this study examines the dynamic nature of marketing outsourcing from the right holder and agency perspectives in an overlooked setting. Research methods: Qualitative data was generated from semi-structured interviews with marketing managers from 30 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Similar to other business sectors, the sport industry has also seen significant outsourcing of sales and marketing management in a variety of settings (Burden and Li, 2009;Dreier, 2011;Dietl et al, 2017;Lee et al, 2016;Lee and Walsh, 2011;Muret, 2011aMuret, ,b, 2013Popp, 2014;Scanlan, 2017;Schoettle, 2012;Zullo et al, 2014). The decision to outsource sales management has been examined extensively utilizing a variety of sport organizations as cases, such as European football (Dietl et al, 2017;Manoli and Hodgkinson, 2017), minor league baseball (Burden and Li, 2009) and National Collegiate Athletic Association departments (Lee et al, 2016;Lee and Walsh, 2011;Popp and McEvoy, 2012;Walker et al, 2009;Zullo et al, 2014). These prior studies result in two foci.…”
Section: Social Exchange Theory and Sales Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other business sectors, the sport industry has also seen significant outsourcing of sales and marketing management in a variety of settings (Burden and Li, 2009;Dreier, 2011;Dietl et al, 2017;Lee et al, 2016;Lee and Walsh, 2011;Muret, 2011aMuret, ,b, 2013Popp, 2014;Scanlan, 2017;Schoettle, 2012;Zullo et al, 2014). The decision to outsource sales management has been examined extensively utilizing a variety of sport organizations as cases, such as European football (Dietl et al, 2017;Manoli and Hodgkinson, 2017), minor league baseball (Burden and Li, 2009) and National Collegiate Athletic Association departments (Lee et al, 2016;Lee and Walsh, 2011;Popp and McEvoy, 2012;Walker et al, 2009;Zullo et al, 2014). These prior studies result in two foci.…”
Section: Social Exchange Theory and Sales Interactionsmentioning
confidence: 99%
“…For example, Walker et al (2009) surveyed collegiate marketing administrators who work with outsourced agencies within their athletic department and found a significant positive relationship between communication satisfaction measures and organizational commitment. Similarly, Lee et al (2016) and Manoli and Hodgkinson (2017) conducted qualitative interviews with organizational members to examine relationships between key members of both the sport organization and the employees of an outsourced company hired to sell sponsorship or tickets.…”
Section: Social Exchange Theory and Sales Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the significant commercial growth of the industry, marketing communication aspects such as sponsorship, relationship marketing and management, and brand management have also received considerable attention (McCarthy et al, 2014). EPL clubs are often considered to be remarkably advanced in those aspects when compared with both other sports leagues and other industry sectors (Manoli and Hodgkinson, 2017;Manoli and Kenyon, 2018). Taking this into consideration, focusing on EPL clubs would allow for insights to be gained from industry leaders working within highly prominent organisations.…”
Section: Setting and Samplementioning
confidence: 99%
“…Copeland (1996) also found that most sponsorship arrangements were far from equitable, yet this does not dissuade corporations from spending resources to find a perfect event to match their image as well as researching demographic and psychographic profiles of participants (Irwin, 1995;Pappu & Cornwell, 2014). This helps in gauging the level of brand exposure, quality of the sport concerned, exclusivity arrangements and quantity and quality of broadcast exposure (Wilson, Westberg, & Henseler, 2011;Manoli & Hodgkinson, 2017).…”
Section: Multiple Alternative Revenue Streamsmentioning
confidence: 99%